Efficacy of Bacillus clausii and Saccharomyces boulardii in Treatment of Acute Rotaviral Diarrhea in Pediatric Patients - Salloju Vineeth; Shagamreddy Saireddy; Thallapalli Keerthi; Prasantha K. Mantada (Indonesian Journal of Clinical Pharmacy, 2017)
Diarrhea disease is considered as major health problem in developing countries. Rotavirus is the most common identifiable viral cause of diarrhea in all children and belongs to Reoviridae family. Rotavirus infection occasionally leads to severe dehydration in infants and children. The objective of the study is to assess the efficacy of Bacillus clausii and Saccharomyces boulardii on the treatment of rotaviral diarrhea, and also to assess its effect on vomiting and fever in pediatric patients. This study conducted at Rainbow Children’s Hospital, Hyderabad, India, from January 2016 until June 2016 and adopts prospective observational parallel study design. From 104 patients enrolled, 80 fulfilled inclusion criteria and 24 were excluded from the study. Patients were divided into two groups based on the treatment. Group I patients were treated with Bacillus clausii and Group II patients were treated with Saccharomyces boulardii. Total mean duration of diarrhea was significantly shorter in Group II (S. boulardii) in comparison with Group I (B. clausii). S. boulardii significantly (p≤0.005) decreased the duration of diarrhea which is 25.2 hours over B. clausii. Both probiotic preparations were equal in efficacy on treating the vomiting and fever (p≥0.005). S. boulardii and B. clausii were well accepted and tolerated by the children and there were no reports of any adverse effects during the study period.Keywords: Bacillus clausii, probiotics, rotaviral diarrhea, Saccharomyces boulardii Efektivitas Bacillus clausii dan Saccharomyces boulardii dalam Pengobatan Diare Akut akibat Rotavirus pada Pasien AnakAbstrakPenyakit diare merupakan salah satu masalah kesehatan yang paling utama di negara-negara berkembang. Rotavirus merupakan virus famili Reoviridae yang umumnya menjadi penyebab diare pada anak. Infeksi rotavirus dapat menyebabkan dehidrasi berat pada bayi dan anak-anak. Tujuan penelitian ini adalah untuk mengukur efektivitas Bacillus clausii dan Saccharomyces boulardii pada pengobatan diare rotavirus dan juga untuk menilai pengaruhnya terhadap muntah dan demam pada pasien anak-anak. Studi ini dilakukan di Rumah Sakit Rainbow Children, Hyderabad, India, pada bulan Januari–Juni 2016 dan menggunakan desain penelitian paralel observasional prospektif. Dari 104 pasien yang terdaftar, sebanyak 80 pasien memenuhi kriteria inklusi dan 24 pasien masuk ke dalam kriteria eksklusi. Pasien dibagi ke dalam dua kelompok berdasarkan pengobatan. Kelompok I merupakan pasien yang diberikan Bacillus clausii dan Kelompok II merupakan pasien yang diberikan Saccharomyces boulardii. Durasi rata-rata diare spada Kelompok II secara signifikan lebih pendek dibandingkan Kelompok I. S. boulardii secara signifikan menurunkan durasi diare (p≤0.005) yaitu 25,2 jam lebih cepat dari B. clausii. Kedua preparat probiotik sama efektifnya dalam mengobati muntah dan demam (p≥0.005). S. boulardii dan B. clausii dapat diterima dengan baik dan ditoleransi oleh anak-anak, serta tidak ada laporan tentang efek samping selama masa studi.Kata kunci: Bacillus clausii, diare rotavirus, probiotik, Saccharomyces boulardii